Social participation and cognitive activities as explanation factor for the association between income and self-rated health for older adults - Buß, A. M.; Wittmann, F. G.; Pabst, A.; Luppa, M.; Oey, A.; Blotenberg, I.; Cardona, M. I.; Weise, S.; Bauer, A.; Kosilek, R. P.; Bader, F.; Brettschneider, C.; et al. (Frontiers in Public Health, 2024)
IntroductionHealth disparities pose a considerable challenge for older adults individuals, particularly those with a heightened risk of developing dementia. Discrepancies in health status among various income brackets are only partially attributable to structural factors such as working and living conditions or the quality of food. The aim of this study was therefore to explore whether and to what extent various health-promoting behaviors can explain the association between household income and self-rated health among older people at risk of dementia.MethodsThe sample consisted of 845 participants (average age 68.9 years; 52.6% female) from the AgeWell.de study, an intervention trial aiming to preserve cognitive function. The participants exhibited an increased risk of dementia, defined by a CAIDE (Cardiovascular Risk Factors, Aging and Dementia) score of at least nine points. To explore the relationship between household income and self-rated health, measured using the EQ-5D-VAS, a regression analysis was conducted. This association was then examined using four mediation analyses that included health-promoting behaviors such as fruit and vegetable consumption, social participation, physical activities, and cognitive activities.ResultsThe results reveal a positive association between higher income and self-rated health. This relationship is mediated by social participation. Additionally, cognitive activities were found to partially mediate this correlation. Neither physical activities nor fruit and vegetable consumption could account for the association between income and self-rated health.ConclusionThe findings have the potential to advance research on the correlation between income and health among older age cohorts at risk of developing dementia. They highlight the potential significance of social engagement and cognitive activities for health and may inspire the development of strategies aimed at enhancing accessibility to activities such as cultural events, educational institutions, and participation in courses for a wider audience.